2021
DOI: 10.3390/diagnostics11091625
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Importance of IL-6, IL-8, and TNF-α in Patients with Ovarian Carcinoma and Benign Cystic Lesions

Abstract: The exact pathogenesis and influence of various cytokines in patients with ovarian lesions remains unclear. Hence, this study aimed to investigate whether IL-6, IL-8, and TNF-α could be considered as new useful markers for diagnosis of ovarian cancer. 63 women diagnosed with ovarian cancer (OC) and 53 patients with benign ovarian cystic (BOC) lesions were included in this study. Serum levels of IL-6, IL-8, and TNF-α were measured using ELISA. Statistical comparisons were made using the Mann–Whitney U test and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Preclinical models are proposed to understand possible mechanistic functions that may interlink these microorganisms with local and systemic inflammation during EOC development. C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) serum markers have shown to be higher in women with malignant ovarian tumors while there is uncertainty if serum levels are associated with unique GI microbes [ 27 , 28 , 29 , 30 ]. Thus, the purpose of this research was to explore the influences of GI microbiota dysbiosis on inflammatory markers during EOC development and progression using a mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical models are proposed to understand possible mechanistic functions that may interlink these microorganisms with local and systemic inflammation during EOC development. C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) serum markers have shown to be higher in women with malignant ovarian tumors while there is uncertainty if serum levels are associated with unique GI microbes [ 27 , 28 , 29 , 30 ]. Thus, the purpose of this research was to explore the influences of GI microbiota dysbiosis on inflammatory markers during EOC development and progression using a mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 and IL-8 in particular are proinflammatory cytokines that are biomarkers of ongoing inflammation and known to negatively affect adaptive immune responses. They have been shown previously to be elevated in the sera of cancer patients (32,33) and to modulate response to immunotherapy (34,35).…”
Section: Discussionmentioning
confidence: 91%
“…IL-6 and IL-8 in particular are proinflammatory cytokines that are biomarkers of ongoing inflammation and known to negatively affect adaptive immune responses. They have been shown previously to be elevated in the sera of cancer patients (32, 33) and to modulate response to immunotherapy (34, 35). More recently they have also been found in premalignant disease, such as in individuals with cervical epithelial neoplasms (36), oral premalignant lesions (37, 38), and Barrett’s esophagus (39).…”
Section: Discussionmentioning
confidence: 96%
“…Women diagnosed with HGSOC have consistently shown elevated circulating levels of IL-6, IL-8, and TNF-α. Clinical data have indicated that IL-6 and IL-8 are significantly amplified between benign ovarian tumors and HGSOCs [163,164]. Studies have shown that innate and activated immune cells are largely responsible for cytokine secretion.…”
Section: Cytokinesmentioning
confidence: 99%